PROPERTY AND EQUIPMENT DEPRECIATION APPLICATIONS USING POST TURBO - Nana Nana; Susi Wagiyati.P, Skom, MM (Jurnal Sistem Informasi, 2001)
This writing discusses the problems using the methods of depreciation of fixed assetsused by companies to determine how much depreciation of their fixed assets in oneyear or more to run their companies.